Methodological approaches to assessing the restructuring of economic entities - Sindarov, Vasili R.; Samal, Sergei A. (Journal of the Belarusian State University. Economics, 2022)
The expediency of the analysis of indicators of strategic and financial sustainability of the enterprise is substantiated. An integrated approach to the definition of the concept of «restructuring» is proposed. The main types of restructuring have been studied. Their common and specific features are revealed. The prerequisites and stages of the restructuring have been established. The problems of personnel transformation as one of the main components of the overall restructuring of the enterprise are considered.